2005
DOI: 10.1158/1078-0432.ccr-04-1877
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Inhibits Prostate Cancer Growth: Evidence of a Cyclooxygenase-2-Independent Mechanism

Abstract: Purpose: Selective cyclooxygenase-2 (COX-2) inhibitors may suppress carcinogenesis by both COX-2-dependent and COX-2-independent mechanisms. The primary purpose of this study was to evaluate whether celecoxib or rofecoxib, two widely used selective COX-2 inhibitors, possess COX-2-independent antitumor activity.Experimental Design: PC3 and LNCaP human prostate cancer cell lines were used to investigate the growth inhibitory effects of selective COX-2 inhibitors in vitro. To complement these studies, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
131
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 38 publications
14
131
1
4
Order By: Relevance
“…However, no consensus exists concerning the underlying molecular mechanisms of these effects. Consistent with previous studies [36,45,46] , our results demonstrated that celecoxib induced G 0 /G 1 cell cycle arrest in HNE1 and CNE1-LMP1 cell lines and that this arrest was accompanied by the down-regulation of Cyclin D1 [12,[45][46][47] , which is one of the major cyclins known to be upregulated in cancers. Cyclin D1 activates Cyclin Dependent Kinase 2 (CDK2) and CDK4, leading to the phosphorylation of the retinoblastoma protein (pRb), which forces its release from the E2F transcription factor.…”
Section: Discussionsupporting
confidence: 92%
“…However, no consensus exists concerning the underlying molecular mechanisms of these effects. Consistent with previous studies [36,45,46] , our results demonstrated that celecoxib induced G 0 /G 1 cell cycle arrest in HNE1 and CNE1-LMP1 cell lines and that this arrest was accompanied by the down-regulation of Cyclin D1 [12,[45][46][47] , which is one of the major cyclins known to be upregulated in cancers. Cyclin D1 activates Cyclin Dependent Kinase 2 (CDK2) and CDK4, leading to the phosphorylation of the retinoblastoma protein (pRb), which forces its release from the E2F transcription factor.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that greater antitumor activity and possibly tumor regression would occur with longer COX inhibitor treatment in mice. In mice with human prostate cancer xenografts, celecoxib caused much more dramatic antitumor effects after 25 days of treatment than after 14 days of treatment (19). In dogs with TCC who have tumor remission with COX inhibitor treatment, tumor regression is observed after f4 weeks of treatment and lifelong COX inhibitor therapy seems necessary.…”
Section: Discussionmentioning
confidence: 99%
“…First, celecoxib has been shown to inhibit growth of cell lines that are deficient for COX-2 expression (12,13). Second, treatment with celecoxib resulted in growth inhibition of xenografts of COX-2-deficient colorectal and prostate cancer cell lines in nude mice (8,14). Third, concentration of celecoxib needed for growth inhibition in vitro is several orders of magnitude higher than the concentration at which COX-2 is inhibited (15,16).…”
Section: Introductionmentioning
confidence: 99%